The politics of expertise how NGOs shaped modern Britain - Hilton, Matthew; McKay, James; Crowson, Nicholas; Mouhot, Jean-Francois (Oxford University Press, 2013)
"The Politics of Expertise offers a challenging new interpretation of politics in contemporary Britain, through an examination of non-governmental organisations. Using specific case studies of the homelessness, environment, and international aid and development sectors, it demonstrates how politics and political activism has changed over the last half century" -- Provided by publisher.